Quantifying motion and `T` dominance of elite squash players - Buote, K.; Jomha, N.; Adeeb, S. (Journal of Sport and Human Performance, 2016)
Advances in video analysis technology expand the realm of possibility for analyzing sport tactics and motion. Video analysis techniques are especially effective in squash due to the small, well-lit, defined court, paired with an ever-growing video collection of elite tournament matches. The availability of matches enables a new methodology that requires no special setup, but only uses video analysis software and the recorded matches that are conveniently filmed for entertainment purposes. This paper presents and evaluates this new methodology that encompasses distance travelled, velocities and speeds attained, court position, and `T` dominance in elite squash. The method was validated when results were compared to previous studies, and a correlation between world rank and court dominance was measured for the first time. A strong correlation (r= 0.64,p<0.001) was found between world rank and average distance from an optimal court position known as the `T` of the squash court.